Tantangan Perkembangan Oikumene di Indonesia - Artariah; Meditatio Situmorang (Publisher STPKat, 2024)
The ecumenical movement in Indonesia is a strategic effort to strengthen the unity of Christian churches from various denominations amidst the complexity of religious, cultural, and ethnic diversity. This paper explores the internal and external challenges faced in the development of ecumenism, including doctrinal differences, leadership conflicts, political, social, cultural pressures, as well as issues of pluralism and interfaith relations. Using the literature study method, this research presents the history of the ecumenical movement in Indonesia, starting from the era of the Council of Churches in Indonesia (DGI) until its transformation into the Persekutuan Gereja-Gereja di Indonesia (PGI). Various initiatives have strengthened the movement, such as the Oikumene Month program, the drafting of a common church order, collective diakonia projects, and interfaith cooperation. Inclusive theological education and inter-denominational dialog were also identified as key in dealing with differences and building harmony. With an approach based on love, solidarity and respect for diversity, the ecumenical movement has great potential to become an important pillar in promoting Christian unity and social harmony in plural Indonesia.